Comparative assessment of ISSR, DAMD and RAPD markers for evalu-ation of genetic diversity of gerbera (Gerbera jamesonii Bolus ex Hooker f.) cultivars - Saidi, Abbas (Acta agriculturae Slovenica, 2023)
Genetic diversity is the best way to improve available genetic resources for breeding programs in gerbera. In present study, genetic diversity of 22 gerbera cultivars was investigated using inter-simple sequence repeat (ISSR), directly amplified minisatellite DNA (DAMD), and Random Amplified Polymorphic DNA (RAPD) markers. Average polymorphism information content (PIC) for ISSR, DAMD and RAPD mark-ers was 0.40, 0.41 and 0.40, respectively. Cluster analysis for ISSR, DAMD and RAPD divided the cultivars into three dis-tinct clusters. The comparative analysis of the three markers (ISSR, DAMD and RAPD) showed that DAMD had superior-ity over RAPD and ISSR in characterization of genetic diver-sity in Gerbera. To our knowledge, this is the first report of a comparison of performance among DAMD, ISSR and RAPD techniques on a set of gerbera genotypes. Overall, our results showed that DAMD markers well represented different geno-types of gerbera diversity.
Keywords: cultivars; DAMD; genetic diversity; genetska raznolikost; genetski markerji; Gerbera; ISSR; RAPD markerji; RAPD markers; sorte